Narrative Modes in Acousmatic Music. Issue 3 (11th November 2016) - Andean, James
Abstract : Beginning with a brief overview of acousmatic narrative, this article proposes that in listening to acousmatic music we select and move between distinct narrative modes, according to the requirements and implications of a given work, or shifting between modes as the work progresses. Similarities and differences with existing theory are considered. Ten narrative modes are proposed as relevant for acousmatic music and discussed. Finally, the appearance of narrative archetypes across multiple modes is considered, as well as similarities across other musics and other fields.